Happiness and Unhappiness Stoic Tourist in Bali - Ariana, Nyoman; Antara, Ketut; Panca, Wayan Agung; Yudiastina, I Gusti Bagus Arya; Suryawan, I Komang Budi (E-Journal of Tourism, 2024)
Stoicism is a philosophy that teaches the creation of a happy life. From a tourism perspective, stoicism is the primary goal of tourists visiting a tourist destination. However, some tourists visiting a destination have the opposite experience, feeling uncomfortable, anxious, angry, or even stressed while traveling. Therefore, it is essential to delve deeper into the connection between Stoic behavior and foreign tourists (foreign tourists) through research. Notably, research is needed on the stoic behavior of foreign tourists who enjoy services and products while traveling in Bali. Based on this, this research aims to analyze tourist happiness associated with the travel experience. Data collection methods include interviews, observations, and documentary studies. Respondents are European foreign tourists visiting Bali. The method used is qualitative descriptive analysis. Data analysis uses NVivo to answer the factors influencing Stoic tourists in Bali. This research found eight factors of happiness with the highest percentage. These factors include friendly people, beautiful nature, many tourist activities, delicious food, beautiful culture, a positive vibe, many experiences, and everything in Bali. In the future, stoic tourists will require more massive amplification so that tourism in Bali can be of higher quality and sustainable.